Synthesis, structural analysis, upconversion luminescence and magnetic properties of Ho3+/Yb3+ co-doped GdVO4 nanophosphor - Thakur H.; Singh B.P.; Kumar R.; Gathania A.K.; Singh S.K.; Singh R.K. (My University, 2025)
Herein, we report a magneto-luminescent nanoparticle (NPs) GdVO4: Ho3+, Yb3+ which is paramagnetic in nature and can emit red emission under NIR excitation. Such magneto-luminescent material may serve potentially as a bi-functional probe (optical/magnetic) for bio-imaging applications. Material has been synthesized using a facile sol-gel technique. The structure and morphology of the synthesized NPs were investigated employing X-ray diffraction, scanning electron microscopy, transmission electron microscopy and Raman spectroscopy techniques. Co-doped GdVO4 NPs crystalizes into tetragonal crystal structure with space group I41/amd. Nonlinear photon upconversion properties of co-doped materials were studied under 980 nm NIR laser excitation. The intense upconversion emission peaks arise at ~543 nm and ~653 nm due to electronic transition (5S2→ 5I8) and (5I5→5I8) of Ho3+, respectively and Yb3+ act as the sensitizer. Optimized concentration i.e. 1 mol% Ho3+/10 mol% Yb3+ gives prominent red emission. From the laser input power dependence studies, three-photon involvements were observed for the green and red bands. A possible mechanism for energy transfer and for possible transitions is also suggested and discussed in details using an energy level diagram. In addition to the excellent optical emission, the NPs show paramagnetic behaviour as well which was confirmed by vibrating sample magnetometer (VSM) studies. Since the prepared nano phosphor materials show the brilliant red upconversion emission under NIR excitation. This may be useful in red color emitter in the display such as LEDs and in bioimaging of the biomolecules. Also, Gd3+ based host gives its paramagnetic character which further promotes its utility in MRI applications. © 2020 Elsevier B.V.